Validation of Self-reported Opioid Agonist Treatment Among People Who Inject Drugs Using Prescription Dispensation Records. Issue 2 (12th November 2021) - Bouck, Zachary; Tricco, Andrea C.; Rosella, Laura C.; Ling, Vicki; Gomes, Tara; Tadrous, Mina; Fox, Matthew P.; Scheim, Ayden I.; Werb, Dan
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Studies of people who inject drugs (PWID) commonly use questionnaires to determine whether participants are currently, or have recently been, on opioid agonist treatment for opioid use disorder. However, these previously unvalidated self-reported treatment measures may be susceptible to inaccurate reporting. Methods: We linked baseline questionnaire data from 521 PWID in the Ontario integrated Supervised Injection Services cohort in Toronto (November 2018–March 2020) with record-level health administrative data. We assessed the validity (sensitivity, specificity, positive and negative predictive value [PPV and NPV]) of self-reported recent (in the past 6 months) and current (as of interview) opioid agonist treatment with methadone or buprenorphine–naloxone relative to prescription dispensation records from a provincial narcotics monitoring system, considered the reference standard. Results: For self-reported recent opioid agonist treatment, sensitivity was 78% (95% CI = 72, 83), specificity was 90% (95% CI = 86, 94), PPV was 90% (95% CI = 85, 93), and NPV was 79% (95% CI = 74, 84). For self-reported current opioid agonist treatment, sensitivity was 84% (95% CI = 78, 90), specificity was 87% (95% CI = 83, 91), PPV was 74% (95% CI = 67, 81), and NPV was 93% (95% CI = 89, 95). Conclusions: Self-reported opioid agonist treatment measures were fairly accurate among PWID, with some exceptions. Inaccurate recall due to a lengthy lookback window may explain underreporting of recent treatment, whereas social desirability bias may have led to overreporting of current treatment. These validation data could be used in future studies of PWID to adjust for misclassification in similar self-reported treatment measures.